The Nuts and Bolts for Effective Literacy and Numeracy Instruction in Early Childhood - Inyega, Hellen N.; Inyega, Justus O. (Papers in Education and Development, 2018)
This paper, using the documentary analysis approach, identifies ' six Ts ' for improving early literacy and numeracy instruction as tongue, teachers, texts, time-on-task, technology and testing. It answers the question: What are the nuts and bolts needed to revamp early childhood teacher education and teacher professional development for greater impact and improved outcomes in early literacy and numeracy? Key findings affirm that all the six Ts must be addressed collectively for lasting impact on early literacy and numeracy instruction.